Analisis Kepuasan Konsumen Memediasi Pengalaman Belanja Online Dalam Membentuk Loyalitas Pelanggan (Survei E-Commerce Bukalapak) - Surahman, Zakilla Stephania; Sunarya, Ery (Peneliti.net, 2024)
Current technological developments require every human being to continue to innovate, including when it comes to shopping with the aim of making it easier and faster. e-commerce is one solution to overcome the problem of efficiency in carrying out buying and selling transactions. So Bukalapak e-commerce is one e-commerce that is not always people's main choice in using e-commerce because of the large number of e-commerce that currently exist. Thus, this will have an impact on decreasing consumer loyalty towards Bukalapak e-commerce. The purpose of this research is to determine the mediating influence of consumer satisfaction in the relationship between online shopping experience and customer loyalty interest. The results show that Bukalapak e-commerce has succeeded in building a good online shopping experience, consumer satisfaction and customer loyaliy in the eyes of consumers.